CN106948005A - The manufacture method of monocrystalline lithium tantalate substrate - Google Patents

The manufacture method of monocrystalline lithium tantalate substrate Download PDF

Info

Publication number
CN106948005A
CN106948005A CN201710003835.6A CN201710003835A CN106948005A CN 106948005 A CN106948005 A CN 106948005A CN 201710003835 A CN201710003835 A CN 201710003835A CN 106948005 A CN106948005 A CN 106948005A
Authority
CN
China
Prior art keywords
lithium tantalate
substrate
single crystal
tantalate substrate
wavelength
Prior art date
Legal status (The legal status is an assumption and is not a legal conclusion. Google has not performed a legal analysis and makes no representation as to the accuracy of the status listed.)
Granted
Application number
CN201710003835.6A
Other languages
Chinese (zh)
Other versions
CN106948005B (en
Inventor
阿部淳
Current Assignee (The listed assignees may be inaccurate. Google has not performed a legal analysis and makes no representation or warranty as to the accuracy of the list.)
Shin-Etsu Chemical Co Ltd
Original Assignee
Shin-Etsu Chemical Co Ltd
Priority date (The priority date is an assumption and is not a legal conclusion. Google has not performed a legal analysis and makes no representation as to the accuracy of the date listed.)
Filing date
Publication date
Application filed by Shin-Etsu Chemical Co Ltd filed Critical Shin-Etsu Chemical Co Ltd
Publication of CN106948005A publication Critical patent/CN106948005A/en
Application granted granted Critical
Publication of CN106948005B publication Critical patent/CN106948005B/en
Active legal-status Critical Current
Anticipated expiration legal-status Critical

Links

Classifications

    • C—CHEMISTRY; METALLURGY
    • C30—CRYSTAL GROWTH
    • C30B—SINGLE-CRYSTAL GROWTH; UNIDIRECTIONAL SOLIDIFICATION OF EUTECTIC MATERIAL OR UNIDIRECTIONAL DEMIXING OF EUTECTOID MATERIAL; REFINING BY ZONE-MELTING OF MATERIAL; PRODUCTION OF A HOMOGENEOUS POLYCRYSTALLINE MATERIAL WITH DEFINED STRUCTURE; SINGLE CRYSTALS OR HOMOGENEOUS POLYCRYSTALLINE MATERIAL WITH DEFINED STRUCTURE; AFTER-TREATMENT OF SINGLE CRYSTALS OR A HOMOGENEOUS POLYCRYSTALLINE MATERIAL WITH DEFINED STRUCTURE; APPARATUS THEREFOR
    • C30B29/00—Single crystals or homogeneous polycrystalline material with defined structure characterised by the material or by their shape
    • C30B29/10—Inorganic compounds or compositions
    • C30B29/16—Oxides
    • C30B29/22—Complex oxides
    • C30B29/30—Niobates; Vanadates; Tantalates
    • C—CHEMISTRY; METALLURGY
    • C30—CRYSTAL GROWTH
    • C30B—SINGLE-CRYSTAL GROWTH; UNIDIRECTIONAL SOLIDIFICATION OF EUTECTIC MATERIAL OR UNIDIRECTIONAL DEMIXING OF EUTECTOID MATERIAL; REFINING BY ZONE-MELTING OF MATERIAL; PRODUCTION OF A HOMOGENEOUS POLYCRYSTALLINE MATERIAL WITH DEFINED STRUCTURE; SINGLE CRYSTALS OR HOMOGENEOUS POLYCRYSTALLINE MATERIAL WITH DEFINED STRUCTURE; AFTER-TREATMENT OF SINGLE CRYSTALS OR A HOMOGENEOUS POLYCRYSTALLINE MATERIAL WITH DEFINED STRUCTURE; APPARATUS THEREFOR
    • C30B33/00—After-treatment of single crystals or homogeneous polycrystalline material with defined structure
    • C30B33/02—Heat treatment

Landscapes

  • Chemical & Material Sciences (AREA)
  • Engineering & Computer Science (AREA)
  • Crystallography & Structural Chemistry (AREA)
  • Materials Engineering (AREA)
  • Metallurgy (AREA)
  • Organic Chemistry (AREA)
  • Inorganic Chemistry (AREA)
  • Physics & Mathematics (AREA)
  • Thermal Sciences (AREA)
  • Crystals, And After-Treatments Of Crystals (AREA)
  • Surface Acoustic Wave Elements And Circuit Networks Thereof (AREA)

Abstract

本发明提供一种不需减压工序的,均质性高的体积电阻率为1×1010Ω·cm以上,1×1012Ω·cm未满的钽酸锂单晶基板的制造方法。本发明包括,将体积电阻率为1×1012Ω·cm以上,且单区域构造的钽酸锂单晶基板,常压下,氢氛围中,400℃以上,居里温度以下的温度进行热处理的第一工序和,将该第一工序处理的钽酸锂单晶基板,与碳酸锂一起,常压下,氢或氮氛围中,400℃以上,居里温度以下的温度进行热处理的第二工序。The present invention provides a method for manufacturing a lithium tantalate single crystal substrate with high homogeneity and a volume resistivity of more than 1×10 10 Ω·cm and less than 1×10 12 Ω·cm without a decompression process. The present invention includes heat-treating a lithium tantalate single crystal substrate with a volume resistivity of 1×10 12 Ω·cm or more and a single-domain structure under normal pressure and in a hydrogen atmosphere at a temperature above 400°C and below the Curie temperature The first step and the second step of heat-treating the lithium tantalate single crystal substrate processed in the first step together with lithium carbonate under normal pressure in a hydrogen or nitrogen atmosphere at a temperature above 400°C and below the Curie temperature process.

Description

钽酸锂单晶基板的制造方法Manufacturing method of lithium tantalate single crystal substrate

技术领域technical field

本发明涉及在表面弹性波元件中使用的钽酸锂单晶基板的制造方法。The present invention relates to a method of manufacturing a lithium tantalate single crystal substrate used in a surface acoustic wave device.

背景技术Background technique

钽酸锂(LiTaO3;LT)单晶,具有压电性,被作为弹性表面波元件的压电基板使用。另一方面,钽酸锂单晶也具有热电性,温度发生变化,表面电荷发生。这样的热电性,在作为传感器利用的场合虽然存在,但是,在将钽酸锂结晶作为弹性表面波元件的压电基板使用的场合,该热电性会成为问题。Lithium tantalate (LiTaO 3 ; LT) single crystal has piezoelectricity and is used as a piezoelectric substrate of surface acoustic wave devices. On the other hand, lithium tantalate single crystal also has pyroelectricity, and the temperature changes, and the surface charge occurs. Such pyroelectricity exists when it is used as a sensor, but when a lithium tantalate crystal is used as a piezoelectric substrate of a surface acoustic wave element, this pyroelectricity becomes a problem.

例如,在由于温度变化压电基板带电的场合,在压电基板内发生静电放电,会成为破裂以及断裂的原因。此外,在压电基板的表面形成的电极有可能会由于静电而短路。For example, when the piezoelectric substrate is charged due to a temperature change, electrostatic discharge occurs in the piezoelectric substrate, causing cracks and fractures. In addition, electrodes formed on the surface of the piezoelectric substrate may be short-circuited by static electricity.

因此,作为对钽酸锂基板的带电进行抑制的目的,认为钽酸锂基板要在居里温度以下的温度进行还原处理,这一方法被广泛利用(专利文献1~5以及非专利文献1参照)。Therefore, for the purpose of suppressing the electrification of the lithium tantalate substrate, it is considered that the lithium tantalate substrate should be reduced at a temperature below the Curie temperature, and this method is widely used (Patent Documents 1 to 5 and Non-Patent Document 1 refer to ).

例如,专利文献1中,记载了在还原性氛围中与金属蒸气一起进行热处理的方法,在专利文献2中,记载了在还原性氛围中,在居里温度以上使还原处理的物质接触而进行热处理的方法。此外,在专利文献3以及4中,埋入Al和Al2O3的混合粉末中进行热处理的方法。由此,这样的还原处理了的钽酸锂基板的体积电阻率为,1×1012Ω·cm未满,使将热电性进行有效地抑制成为可能。For example, Patent Document 1 describes a method of heat-treating together with metal vapor in a reducing atmosphere, and Patent Document 2 describes performing a heat treatment by contacting a reducing-treated substance at a Curie temperature or higher in a reducing atmosphere. The method of heat treatment. In addition, in Patent Documents 3 and 4, a method of embedding a mixed powder of Al and Al 2 O 3 and performing heat treatment is used. As a result, the volume resistivity of such a reduction-treated lithium tantalate substrate is less than 1×10 12 Ω·cm, making it possible to effectively suppress pyroelectricity.

此外,还原处理实施了的钽酸锂基板,要进行黑色化是已知的。通常的钽酸锂单晶基板在波长365nm的光透过率为70~80%左右,还原处理实施了的钽酸锂单晶基板,在波长365nm的光透过率为50~60%左右,这样的光透过率抑制在弹性表面波元件制造时的光刻工序中是有利的。In addition, it is known that a lithium tantalate substrate subjected to a reduction treatment is blackened. A normal lithium tantalate single crystal substrate has a light transmittance of about 70 to 80% at a wavelength of 365nm, and a lithium tantalate single crystal substrate subjected to reduction treatment has a light transmittance of about 50 to 60% at a wavelength of 365nm. Such suppression of light transmittance is advantageous in the photolithography process in the manufacture of surface acoustic wave devices.

另一方面,该钽酸锂单晶基板中,如例如专利文献6,7记载的那样,有添加铁元素的场合。然后,对在该铁元素添加了的钽酸锂单晶基板进行还原处理的场合,与通常的钽酸锂单晶基板进行原处理的场合相比,会进一步抑制光透过率。铁元素添加了的钽酸锂单晶基板的在波长365nm的光透过率为50%左右,但如将其进行还原处理,波长365nm的光透过率会变为30%左右。On the other hand, in this lithium tantalate single crystal substrate, for example, as described in Patent Documents 6 and 7, iron element may be added. Then, when the reduction treatment is performed on the lithium tantalate single crystal substrate to which the iron element is added, the light transmittance is further suppressed compared with the case where the normal lithium tantalate single crystal substrate is subjected to the original treatment. The light transmittance at a wavelength of 365nm of a lithium tantalate single crystal substrate to which iron is added is about 50%, but if it is reduced, the light transmittance at a wavelength of 365nm becomes about 30%.

现有技术文献prior art literature

专利文献patent documents

专利文献1特开2004-035396Patent Document 1 Japanese Unexamined Publication No. 2004-035396

专利文献2WO 2004/079061Patent document 2WO 2004/079061

专利文献3特开2005-119906号公报Patent Document 3 JP-A-2005-119906

专利文献4特开2005-119908号公报Patent Document 4 JP-A-2005-119908

专利文献5特开2005-314137号公报Patent Document 5 JP-A-2005-314137

专利文献6特开2004-254114号公报Patent Document 6 JP-A-2004-254114

专利文献7WO 2007/046176Patent Document 7 WO 2007/046176

非专利文献non-patent literature

非专利文献1Yan Tao et al.“Formation mechanism of black LiTaO3singlecrystals through chemical reduction.”J.Appl.Cryst.44(2011),158-162Non-Patent Document 1 Yan Tao et al. "Formation mechanism of black LiTaO3 singlecrystals through chemical reduction." J.Appl.Cryst.44(2011), 158-162

但是,作为钽酸锂单晶基板的还原处理方法,使用碱金属化合物的方法是已知的。例如,专利文献5中,记载了与碱金属化合物一起在减压下进行热处理的方法。在非专利文献1中记载了,在氮气氛围下,与Fe和Li2CO3的混合粉末一起热处理的方法。However, a method using an alkali metal compound is known as a reduction treatment method for a lithium tantalate single crystal substrate. For example, Patent Document 5 describes a method of heat-treating an alkali metal compound under reduced pressure. Non-Patent Document 1 describes a method of heat-treating a mixed powder of Fe and Li 2 CO 3 in a nitrogen atmosphere.

但是,这样的使用碱金属化合物的钽酸锂单晶基板的还原处理方法被发现有问题。本发明人,对专利文献5记载的方法,进行再现实验,但是不能进行钽酸锂单晶基板满足的还原处理,没有能抑制热电性。此外,即使按专利文献5记载的方法进行了还原处理,由于减压工序必要,所以生产性差。However, such a reduction treatment method of a lithium tantalate single crystal substrate using an alkali metal compound has been found to be problematic. The inventors of the present invention carried out a reproduction experiment with the method described in Patent Document 5, but the reduction treatment of the lithium tantalate single crystal substrate could not be performed satisfactorily, and the pyroelectricity could not be suppressed. In addition, even if the reduction treatment is performed by the method described in Patent Document 5, the productivity is poor because a depressurization step is necessary.

此外,对非专利文献1记载的方法,本发明者也进行了再现实验,可以进行钽酸锂单晶基板还原处理,但是还原的进行程度不充分,基板表面有色斑,基板的面内方向的均质性差。In addition, the present inventors also carried out reproduction experiments on the method described in Non-Patent Document 1, and the reduction treatment of lithium tantalate single crystal substrates can be performed, but the degree of progress of the reduction is not sufficient, and there are stains on the surface of the substrate, and the in-plane direction of the substrate of poor homogeneity.

所以,本发明的1个的目的为,提供一种不要减压工序的,可以得到均质性的高的,体积电阻率为1×1010Ω·cm以上,1×1012Ω·cm未满的钽酸锂单晶基板的新的还原处理的制造方法。Therefore, one object of the present invention is to provide a product that does not require a depressurization process, can obtain high homogeneity, and has a volume resistivity of 1×10 10 Ω·cm or more, and 1×10 12 Ω·cm or less. A new reduction-processed fabrication method for full LiTaO single crystal substrates.

在制作弹性表面波元件时的光刻工序中,钽酸锂基板的曝光光的透过率为,低的可以形成细微并且正确的图案,优选。一般,光刻中,作为曝光光,使用水银灯的g线(436nm),i线(365nm),KrF准分子激光(248nm),ArF准分子激光(193nm)。特别是,近年,细微化在前进,比i线还短的波长的曝光光多被使用。In the photolithography process when producing a surface acoustic wave device, it is preferable that the transmittance of the exposure light of the lithium tantalate substrate is low so that a fine and accurate pattern can be formed. Generally, in photolithography, g-line (436 nm), i-line (365 nm) of a mercury lamp, KrF excimer laser (248 nm), and ArF excimer laser (193 nm) are used as exposure light. In particular, miniaturization is progressing in recent years, and exposure light with a wavelength shorter than the i-line is often used.

所以,添加铁元素的钽酸锂单晶基板如实施还原处理,波长365nm的光透过率为30%左右,比没有添加铁元素的钽酸锂单晶基板的波长365nm的光透过率低,在光刻工序中有利。通常,钽酸锂单晶基板的光透过率具有越靠短波长一侧越低,越靠长波长侧越高的倾向。Therefore, if the lithium tantalate single crystal substrate with iron added is subjected to reduction treatment, the light transmittance at a wavelength of 365 nm is about 30%, which is lower than the light transmittance at a wavelength of 365 nm of a lithium tantalate single crystal substrate without iron added. , which is beneficial in the photolithography process. Generally, the light transmittance of the lithium tantalate single crystal substrate tends to decrease toward the shorter wavelength side and increase toward the longer wavelength side.

另一方面,由于铁元素的添加或者还原处理,短波长侧的光透过率变低的钽酸锂单晶基板中,长波长侧的光透过率也变低。可以确认,由于铁元素的添加和还原处理,在波长365nm的光透过率变为30%以下的钽酸锂单晶基板中,波长485nm的光透过率变为小于50%。On the other hand, in the lithium tantalate single crystal substrate whose light transmittance on the short-wavelength side becomes low due to addition of iron element or reduction treatment, the light transmittance on the long-wavelength side also becomes low. It was confirmed that the light transmittance at a wavelength of 485 nm became less than 50% in the lithium tantalate single crystal substrate in which the light transmittance at a wavelength of 365 nm became 30% or less due to the addition of iron element and the reduction treatment.

本发明人,对用专利文献2记载的方法进行了铁添加的钽酸锂单晶基板的还原处理进行了测试,确认到,波长365nm的光透过率为30%以下,波长485nm的光透过率为小于50%。The inventors of the present invention tested the reduction treatment of lithium tantalate single crystal substrates to which iron was added by the method described in Patent Document 2, and confirmed that the light transmittance at a wavelength of 365 nm is 30% or less, and the light transmittance at a wavelength of 485 nm is less than 30%. The pass rate is less than 50%.

但是,近年,在表面弹性波元件中,形成梳形电极等,使具有作为元件的功能的功能性基板和为了对电极部的保护等而设置的封装基板为同一材质,此时,由于材料物性一样,表面弹性波元件基板和封装基板和的整合性良好,加工性,安定性的面优良,作为功能性基板使用的材料被作为封装材料使用的场合增加了。However, in recent years, in surface acoustic wave devices, comb-shaped electrodes and the like are formed, and the functional substrate having the function of the device and the packaging substrate provided for protecting the electrode part are made of the same material. Similarly, surface acoustic wave device substrates and packaging substrates are well integrated, processability, and stability are excellent, and materials used as functional substrates are increasingly used as packaging materials.

但是,这样的场合,有长波长侧的光透过率低,表面弹性波元件的制造作业性变差的可能性。功能性基板和封装基板一体化时,用激光进行的调整作业变为必要,此时,如封装基板的调整激光波长处的光透过率低的场合,调整作业困难。However, in such a case, the light transmittance on the long wavelength side is low, and the manufacturing workability of the surface acoustic wave device may be deteriorated. When the functional substrate and the package substrate are integrated, an adjustment operation using a laser becomes necessary, and in this case, if the light transmittance at the adjustment laser wavelength of the package substrate is low, the adjustment operation is difficult.

所以,钽酸锂单晶基板的光透过率,以在与光刻工序中使用的曝光光相比短波长侧低为好,以比光刻工序中使用的曝光光长的波长的领域中尽可能高为优选。Therefore, the light transmittance of the lithium tantalate single crystal substrate should be lower on the shorter wavelength side than the exposure light used in the photolithography process, and in the range of longer wavelengths than the exposure light used in the photolithography process. As high as possible is preferred.

因此,本发明的第2个目的为,提供一种,作为表面弹性波元件的功能性基板,此外作为封装基板也可以良好使用的波长365nm的光透过率为30%以下,波长485nm的光透过率为50%以上的钽酸锂基板的制造方法。Therefore, a second object of the present invention is to provide a light with a wavelength of 485 nm and a light transmittance of 30% or less at a wavelength of 365 nm that can be used well as a functional substrate of a surface acoustic wave device and also as a packaging substrate. A method for manufacturing a lithium tantalate substrate having a transmittance of 50% or more.

发明内容Contents of the invention

本发明为,一种钽酸锂单晶基板的制造方法,所述酸锂单晶基板的体积电阻率为1×1010Ω·cm以上,1×1012Ω·cm未满,其特征在于,具有,将体积电阻率为1×1012Ω·cm以上,并且单区域构造的钽酸锂单晶基板,在常压下,氢氛围中,400℃以上,居里温度以下的温度进行热处理的第一工序和,将在所述第一工序处理的钽酸锂单晶基板,与碳酸锂一起,在常压下,氢或氮氛围中,400℃以上,居里温度以下的温度,进行热处理的第二工序。The present invention is a method for manufacturing a lithium tantalate single crystal substrate. The volume resistivity of the lithium tantalate single crystal substrate is more than 1×10 10 Ω·cm and less than 1×10 12 Ω·cm, characterized in that , having a lithium tantalate single crystal substrate with a volume resistivity of 1×10 12 Ω·cm or more and a single-domain structure, under normal pressure, in a hydrogen atmosphere, for heat treatment at a temperature above 400°C and below the Curie temperature The first process and the lithium tantalate single crystal substrate processed in the first process, together with lithium carbonate, are carried out under normal pressure, in a hydrogen or nitrogen atmosphere, at a temperature above 400°C and below the Curie temperature. The second process of heat treatment.

此外,在本发明的热处理的第一工序中,以使体积电阻率为1×1012Ω·cm以上,并且单区域构造的钽酸锂单晶基板,与在还原性氛围中,居里温度以上的温度,进行热处理的多区域构造的钽酸锂单晶基板进行接触,热处理为优选。In addition, in the first step of the heat treatment of the present invention, the volume resistivity is 1×10 12 Ω·cm or more, and the lithium tantalate single crystal substrate with a single-domain structure has the same Curie temperature in a reducing atmosphere. The above temperature is preferably heat-treated to contact the lithium tantalate single crystal substrate of the multi-domain structure that is heat-treated.

进一步,在本发明的热处理的第二工序中,将在第一工序处理的钽酸锂单晶基板,埋入碳酸锂粉末中为优选,使该热处理在氮氛围中进行为更优选。Furthermore, in the second step of the heat treatment of the present invention, it is preferable to embed the lithium tantalate single crystal substrate processed in the first step into lithium carbonate powder, and it is more preferable to perform the heat treatment in a nitrogen atmosphere.

本发明的钽酸锂单晶基板为,作为添加元素以含铁为优选,在该场合,以铁的含有量为,50ppm~200ppm为优选。The lithium tantalate single crystal substrate of the present invention preferably contains iron as an additive element, and in this case, the iron content is preferably 50 ppm to 200 ppm.

在本发明的制造方法中,可以得到,具有在体积电阻率为1×1010Ω·cm以上,1×1012Ω·cm未满的性质以外,波长365nm中的光透过率为30%以下,波长485nm的光透过率为50%以上的性质的钽酸锂单晶基板。In the production method of the present invention, in addition to having a volume resistivity of 1×10 10 Ω·cm or more and 1×10 12 Ω·cm or less, the light transmittance at a wavelength of 365 nm is 30%. Hereinafter, a lithium tantalate single crystal substrate having a light transmittance of 50% or more at a wavelength of 485 nm.

发明效果Invention effect

根据本发明,减压工序不需要,就可以得到均质性的高的体积电阻率为1×1010Ω·cm以上,1×1012Ω·cm未满的钽酸锂单晶基板。由于该基板的体积电阻率为1×1012Ω·cm未满,可以回避由于温度变化而造成的带电,破碎以及断裂的发生以及电极的短路。According to the present invention, a lithium tantalate single crystal substrate having a homogeneous high volume resistivity of not less than 1×10 10 Ω·cm and less than 1×10 12 Ω·cm can be obtained without a decompression step. Since the volume resistivity of the substrate is less than 1×10 12 Ω·cm, it is possible to avoid electrification due to temperature changes, generation of cracks and fractures, and short-circuiting of electrodes.

进一步,如果对作为添加元素含铁的钽酸锂单晶基板实施本发明的还原处理方法的话,可以得到波长365nm的光透过率为30%以下,波长485nm的光透过率为50%以上的钽酸锂基板。该基板,不仅可以作为表面弹性波元件的功能性基板,也可以作为封装基板良好使用,在封装材料使用的场合,具有调整作业容易优点。Further, if the reduction treatment method of the present invention is implemented on a lithium tantalate single crystal substrate containing iron as an additive element, the light transmittance at a wavelength of 365 nm is 30% or less, and the light transmittance at a wavelength of 485 nm is 50% or more. Lithium tantalate substrate. This substrate can be used well not only as a functional substrate of a surface acoustic wave device but also as a packaging substrate, and has the advantage of easy adjustment work when used as a packaging material.

具体实施方式detailed description

以下,对本发明的一实施方式进行详细说明,但是本发明并不限于此。Hereinafter, an embodiment of the present invention will be described in detail, but the present invention is not limited thereto.

本发明为一种制造,在具有体积电阻率为1×1010Ω·cm以上,1×1012Ω·cm未满的性质之外,还具有波长365nm的光透过率为30%以下,波长485nm的光透过率为50%以上的性质的钽酸锂基板的制造方法。在该制造,首先,准备体积电阻率为1×1012Ω·cm以上,并且为单区域构造的钽酸锂单晶基板。这样的钽酸锂单晶基板为,例如,用切克劳斯基单晶生长法使钽酸锂单晶成长,在对得到的块体进行极化处理的同时,对基板形状进行加工而得到的。The present invention is a production that has a volume resistivity of 1×10 10 Ω·cm or more and 1×10 12 Ω·cm or less, and a light transmittance of 30% or less at a wavelength of 365 nm, A method of manufacturing a lithium tantalate substrate having a light transmittance of 50% or more at a wavelength of 485 nm. In this production, first, a lithium tantalate single crystal substrate having a volume resistivity of 1×10 12 Ω·cm or more and a single domain structure is prepared. Such a lithium tantalate single crystal substrate is obtained, for example, by growing a lithium tantalate single crystal by the Czochralski single crystal growth method, and processing the shape of the substrate while performing polarization treatment on the obtained bulk. of.

在热处理的第一工序,将准备的钽酸锂单晶基板,常压下,氢氛围中,400℃以上,居里温度以下的温度进行热处理。这是由于,热处理如在400℃未满的温度进行,还原不能充分进行,另一方面,如热处理在比居里温度还高的温度进行的场合,会变成多区域构造。此时,氢气的流量,为了能总是有新鲜的氢气存在,以3l/min以上为优选,6l/min以上为更优选。In the first step of heat treatment, the prepared lithium tantalate single crystal substrate is subjected to heat treatment at a temperature above 400° C. and below the Curie temperature under normal pressure and in a hydrogen atmosphere. This is because, if the heat treatment is performed at a temperature lower than 400°C, the reduction will not proceed sufficiently, and on the other hand, if the heat treatment is performed at a temperature higher than the Curie temperature, a multi-domain structure will be formed. At this time, the flow rate of hydrogen is preferably 3 l/min or more, more preferably 6 l/min or more, in order to always have fresh hydrogen.

此外,该第一工序中,以使在氢以及氮等的还原性气氛围中,居里温度以上的温度进行了热处理的多区域构造的钽酸锂单晶基板与准备的钽酸锂单晶基板接触,进行热处理为优选。In addition, in the first step, the lithium tantalate single crystal substrate with the multi-domain structure heat-treated at a temperature above the Curie temperature and the prepared lithium tantalate single crystal It is preferable to heat-treat the substrates in contact with each other.

此时,优选交互重叠配置,以使在还原性气氛围中,在居里温度以上的温度进行了热处理的多区域构造的钽酸锂单晶基板接触准备的钽酸锂单晶基板的表里两面。如此,基板的厚度方向的均质性被提高。At this time, it is preferable to alternately overlap and arrange the multi-domain lithium tantalate single crystal substrates heat-treated at a temperature above the Curie temperature in a reducing atmosphere to contact the front and back of the prepared lithium tantalate single crystal substrates. two sides. In this way, the uniformity in the thickness direction of the substrate is improved.

进一步,作为热处理的第二工序,将结束第一工序结束的基板,与碳酸锂一起,在常压下,氢或氮氛围中,400℃以上,居里温度以下的温度进行热处理。第二工序也由于与第一工序的场合相同的理由,在400℃未满或居里温度以上的温度进行是不好的。此时,氢气或氮气的流量以3l/min以上为优选,以6l/min以上为更优选,这样可以总是有新鲜的气体存在,Furthermore, as the second step of heat treatment, the substrate after the first step is heat-treated together with lithium carbonate at a temperature above 400° C. and below the Curie temperature under normal pressure in a hydrogen or nitrogen atmosphere. For the same reason as in the case of the first step, it is not preferable to perform the second step at a temperature lower than 400° C. or higher than the Curie temperature. At this time, the flow rate of hydrogen or nitrogen is preferably more than 3l/min, more preferably more than 6l/min, so that there can always be fresh gas to exist,

在该第二工序中,氢气和氮气任何一方都可以使用。氮气,安全,设备等的成本可以压低,优选。另一方面,氢气的还原作用强,处理的基板的透过率和体积电阻率有变低的倾向。In this second step, either hydrogen gas or nitrogen gas can be used. The cost of nitrogen, safety, equipment, etc. can be kept down, preferably. On the other hand, the reducing action of hydrogen gas is strong, and the transmittance and volume resistivity of the processed substrate tend to be lowered.

在此,作为第二工序使用的碳酸锂的作用,为在948K以下的温度,部分分解,生成氧化锂,二氧化碳,一氧化碳,该一氧化碳,被认为将Ta5+还原为Ta4+。在此,作为触媒,在碳酸锂之外,也可存在少量的铁等。铁,将生成的二氧化碳分解为一氧化碳,所以可以促进钽酸锂的还原。如在碳酸锂中混入铁,虽然与碳酸锂单体进行还原时相比能促进还原,但是,在碳酸锂以及铁一起进行热处理的场合,基板表面会出现色斑,因此以仅用碳酸锂进行为优选。Here, the role of lithium carbonate used as the second step is to partially decompose at a temperature below 948K to generate lithium oxide, carbon dioxide, and carbon monoxide, and this carbon monoxide is considered to reduce Ta 5+ to Ta 4+ . Here, as a catalyst, a small amount of iron or the like may be present in addition to lithium carbonate. Iron decomposes the generated carbon dioxide into carbon monoxide, so it can promote the reduction of lithium tantalate. If iron is mixed in lithium carbonate, although it can promote the reduction compared with the reduction of lithium carbonate alone, when lithium carbonate and iron are heat treated together, stains will appear on the surface of the substrate, so it is best to use only lithium carbonate. is preferred.

此外,第二工序中,以将在第一工序处理的基板埋入碳酸锂粉末中为优选,优选通过埋入使碳酸锂粉末接触基板的表里两面。多个基板同時处理的场合,只要使基板间存在碳酸锂粉末即可。In addition, in the second step, it is preferable to embed the substrate processed in the first step in the lithium carbonate powder, and it is preferable to make the lithium carbonate powder contact the front and back surfaces of the substrate by embedding. When processing a plurality of substrates at the same time, lithium carbonate powder may be present between the substrates.

第一以及第二工序结束后的基板,根据必要实施研磨等,由此可以得到体积电阻率为1×1010Ω·cm以上,1×1012Ω·cm未满的均质的钽酸锂单晶基板。如体积电阻率比1×1010Ω·cm低,压电特性变差以及有可能招致绝缘破坏。另一方面,如体积电阻率为1×1012Ω·cm以上,易于带电,招致电极的短路等。所以,有必要控制在该数值范围内。如此控制体积电阻率,可以抑制热电性造成的带电,由此,可以防止基板的破碎,断裂以及电极的短路。The substrates after the first and second steps are polished as necessary to obtain homogeneous lithium tantalate with a volume resistivity of 1×10 10 Ω·cm or more and 1×10 12 Ω·cm or less. single crystal substrate. If the volume resistivity is lower than 1×10 10 Ω·cm, piezoelectric characteristics may deteriorate and dielectric breakdown may occur. On the other hand, if the volume resistivity is not less than 1×10 12 Ω·cm, it is easy to be charged and short-circuiting of the electrodes is caused. Therefore, it is necessary to control within this numerical range. By controlling the volume resistivity in this way, charging due to pyroelectricity can be suppressed, thereby preventing cracking and breaking of the substrate and short circuiting of the electrodes.

本发明的钽酸锂单晶基板的制造方法,适用于含有添加元素的钽酸锂单晶基板,特别是,对添加铁元素的钽酸锂单晶基板适宜。在钽酸锂单晶中添加铁,可以在将波长365nm的光透过率抑制为30%以下的同时,可以将波长485nm的光透过率保持在50%以上。此时,铁的含有量,以重量比率如果为50ppm~200ppm,波长365nm的光透过率就可以有效地抑制,但是,如果是50ppm~200ppm的范围外的话,就不能对波长365nm的光透过率进行充分地抑制,波长485nm的光透过率就难以保持在50%以上,而且,压电特性等的诸特性会变差,不优选。The method for manufacturing a lithium tantalate single crystal substrate of the present invention is suitable for a lithium tantalate single crystal substrate containing additive elements, especially suitable for a lithium tantalate single crystal substrate with an added iron element. Adding iron to the lithium tantalate single crystal can keep the light transmittance at a wavelength of 485nm above 50% while suppressing the light transmittance at a wavelength of 365nm to 30% or less. At this time, if the content of iron is 50ppm to 200ppm by weight, the light transmittance at a wavelength of 365nm can be effectively suppressed, but if it is outside the range of 50ppm to 200ppm, it cannot transmit light at a wavelength of 365nm. If the transmissivity is sufficiently suppressed, it is difficult to maintain the light transmittance at a wavelength of 485 nm at 50% or more, and various characteristics such as piezoelectric characteristics will deteriorate, which is not preferable.

虽然不限于在钽酸锂单晶中添加铁的方法,但是,一般说来,在用切克劳斯基单晶生长法生长钽酸锂单晶时,如果在原料融液中添加氧化铁(Fe2O3)等即可。对于作为添加元素含铁的钽酸锂单晶基板,实施本发明的还原处理方法的场合,就可以得到体积电阻率为1×1010Ω·cm以上,1×1012Ω·cm未满的均质的钽酸锂单晶基板。Although it is not limited to the method of adding iron to lithium tantalate single crystals, generally speaking, when growing lithium tantalate single crystals by the Czochralski single crystal growth method, if iron oxide ( Fe 2 O 3 ) etc. can be used. For a lithium tantalate single crystal substrate containing iron as an additive element, when the reduction treatment method of the present invention is implemented, a volume resistivity of 1×10 10 Ω·cm or more and 1×10 12 Ω·cm can be obtained. Homogeneous lithium tantalate single crystal substrate.

此外,对于添加元素为铁的钽酸锂单晶基板,实施本发明的还原处理方法的场合,可以使波长365nm的光透过率为30%以下。如此,对使用比i线(波长365nm)短波长的光源的光刻工序有利,更优选波长365nm的光透过率为25%以下。In addition, when the reduction treatment method of the present invention is carried out on a lithium tantalate single crystal substrate whose additive element is iron, the light transmittance at a wavelength of 365 nm can be reduced to 30% or less. This is advantageous for a photolithography process using a light source with a shorter wavelength than the i-line (wavelength: 365 nm), and the light transmittance at a wavelength of 365 nm is more preferably 25% or less.

进一步,对于作为添加元素为铁的钽酸锂单晶基板,实施本发明的还原处理方法的场合,可以使波长485nm的光透过率为50%以上。如这样,在钽酸锂单晶基板被作为封装材料使用的场合,和功能基板的调整作业会变得容易。Furthermore, when the reduction treatment method of the present invention is carried out on a lithium tantalate single crystal substrate whose additive element is iron, the light transmittance at a wavelength of 485 nm can be made 50% or more. In this way, when the lithium tantalate single crystal substrate is used as a packaging material, adjustment work with the functional substrate becomes easy.

实施例Example

实施例1Example 1

实施例1中,首先,用切克劳斯基单晶生长法使钽酸锂单晶成长,对得到的块体进行极化处理,单区域化后,将其切片得到多枚的基板(原料基板)。此外,将通常的钽酸锂单晶基板暴露在1050℃的氢气中,准备多区域化的基板。In Example 1, at first, lithium tantalate single crystals were grown by the Czochralski single crystal growth method, and the obtained block was subjected to polarization treatment, and after single-regionalization, it was sliced to obtain a plurality of substrates (raw material substrate). In addition, a general lithium tantalate single crystal substrate was exposed to hydrogen gas at 1050°C to prepare a multi-domain substrate.

然后,作为热处理的第一工序,使单区域化的体积电阻率为4.5×1014Ω·cm的钽酸锂单晶基板和多区域化的钽酸锂单晶基板接触,进行常压下,氢100%氛围中,温度570℃的8小时热处理。Then, as the first step of heat treatment, the single-domain lithium tantalate single crystal substrate with a volume resistivity of 4.5×10 14 Ω·cm was brought into contact with the multi-domain lithium tantalate single crystal substrate, and carried out under normal pressure. Heat treatment at 570°C for 8 hours in a 100% hydrogen atmosphere.

进而,作为热处理的第二工序,将第一工序结束的原料基板取出,将该基板埋入碳酸锂粉中。其后,对埋入碳酸锂粉中的基板,在常压下,氢100%氛围中,温度530℃,进行8小时的热处理。Furthermore, as the second step of heat treatment, the raw material substrate after the first step was taken out, and the substrate was embedded in lithium carbonate powder. Thereafter, the substrate embedded in the lithium carbonate powder was heat-treated at 530° C. for 8 hours under normal pressure in an atmosphere of 100% hydrogen.

此外,对结束第一以及第二工序的基板的两面进行研磨,得到厚度0.2mm的钽酸锂单晶基板后,对该钽酸锂单晶基板,测定体积电阻率,其值为2.0×1011Ω·cm。此外,对波长365nm和波长485nm的光透过率进行测定,得知波长365nm的光透过率为60%,波长485nm的光透过率为65%。In addition, after polishing both sides of the substrate that completed the first and second steps to obtain a lithium tantalate single crystal substrate with a thickness of 0.2 mm, the volume resistivity was measured for the lithium tantalate single crystal substrate, and the value was 2.0×10 11 Ω·cm. In addition, the light transmittance at the wavelength of 365 nm and the wavelength of 485 nm was measured, and it was found that the light transmittance at the wavelength of 365 nm was 60%, and the light transmittance at the wavelength of 485 nm was 65%.

实施例2Example 2

实施例2中,首先,用切克劳斯基单晶生长法使以重量比率计含铁元素为100ppm的钽酸锂单晶,得到的块体实施极化处理后,将其切片得到多个枚的基板。In Example 2, at first, use the Czochralski single crystal growth method to make a lithium tantalate single crystal with an iron element of 100 ppm in weight ratio, and after the obtained block is subjected to polarization treatment, it is sliced to obtain a plurality of piece of substrate.

然后,将这些体积电阻率为4.5×1014Ω·cm的基板,作为热处理的第一工序,常压下,氢100%氛围中,温度570℃进行8小时的热处理。Then, these substrates with a volume resistivity of 4.5×10 14 Ω·cm were subjected to heat treatment at 570° C. for 8 hours under normal pressure and in an atmosphere of 100% hydrogen as the first step of heat treatment.

进而,作为热处理的第二工序,将第一工序结束的基板取出,将该基板埋入碳酸锂粉中。其后,将埋入碳酸锂粉中的基板,常压下,氢100%氛围中,温度530℃进行8小时的热处理。Furthermore, as the second step of heat treatment, the substrate after the first step was taken out, and the substrate was embedded in lithium carbonate powder. Thereafter, the substrate embedded in the lithium carbonate powder was heat-treated at 530° C. for 8 hours under normal pressure in an atmosphere of 100% hydrogen.

此外,对第一以及第二工序结束的基板的两面进行研磨,得到厚度0.2mm的钽酸锂单晶基板后,对该含铁元素的钽酸锂单晶基板,进行波长365nm和波长485nm的光透过率进行测定,结果得到波长365nm的光透过率为25%,波长485nm的光透过率为58%。此外,对得到的基板的体积电阻率进行测定,得知其值为1.0×1011Ω·cm。In addition, after polishing both sides of the substrate after the first and second steps to obtain a lithium tantalate single crystal substrate with a thickness of 0.2mm, the iron element-containing lithium tantalate single crystal substrate was subjected to a wavelength of 365nm and a wavelength of 485nm. As a result of measuring the light transmittance, the light transmittance at a wavelength of 365 nm was 25%, and the light transmittance at a wavelength of 485 nm was 58%. Furthermore, the volume resistivity of the obtained substrate was measured and found to be 1.0×10 11 Ω·cm.

实施例3Example 3

实施例3中,首先,用切克劳斯基单晶生长法使以重量比率含有铁元素为100ppm钽酸锂单晶成长,得到的块体进行极化处理(Polling)单区域化后,将其切片得到多枚的基板(原料基板)。此外,使通常的钽酸锂单晶基板暴露于1050℃的氢气,以准备多区域化的基板。In Example 3, first, a single crystal of lithium tantalate containing 100 ppm of iron by weight was grown by the Czochralski single crystal growth method, and the obtained block was subjected to a single-region polarization treatment (Polling), and then By slicing, a plurality of substrates (raw substrates) are obtained. In addition, a general lithium tantalate single crystal substrate was exposed to hydrogen gas at 1050° C. to prepare a multi-domain substrate.

然后,作为热处理的第一工序,使铁元素为100ppm的单区域化的体积电阻率为4.5×1014Ω·cm的钽酸锂单晶基板和多区域化的钽酸锂单晶基板接触,常压下,氢100%氛围中,温度570℃进行8小时的热处理。Then, as the first step of heat treatment, a single-domain lithium tantalate single crystal substrate with an iron element of 100 ppm and a volume resistivity of 4.5×10 14 Ω·cm was brought into contact with a multi-domain lithium tantalate single crystal substrate, Heat treatment was performed at 570° C. for 8 hours in an atmosphere of 100% hydrogen under normal pressure.

进而,使热处理的第二工序和研磨工序以与实施例1相同的条件来进行,厚度0.2mm的钽酸锂单晶基板得到后,对该含铁元素钽酸锂单晶基板,波长365nm和波长485nm的光透过率进行测定,得知波长365nm的光透过率为20%,波长485nm的光透过率为55%。此外,对得到的基板的体积电阻率进行测定,得知其值为5.5×1010Ω·cm。Furthermore, the second step of heat treatment and the grinding step were carried out under the same conditions as in Example 1. After the lithium tantalate single crystal substrate with a thickness of 0.2 mm was obtained, the iron element-containing lithium tantalate single crystal substrate was used at a wavelength of 365 nm and The light transmittance at a wavelength of 485 nm was measured, and it was found that the light transmittance at a wavelength of 365 nm was 20%, and that at a wavelength of 485 nm was 55%. Furthermore, the volume resistivity of the obtained substrate was measured and found to be 5.5×10 10 Ω·cm.

比较例comparative example

比较例1Comparative example 1

比较例1中,首先,用切克劳斯基单晶生长法使钽酸锂单晶成长,得到的块体进行极化处理,单区域化后,将其切片得到多枚的基板(原料基板)。In Comparative Example 1, at first, a lithium tantalate single crystal was grown by the Czochralski single crystal growth method, and the obtained block was subjected to polarization treatment, and after being single-regionalized, it was sliced to obtain a plurality of substrates (raw substrates). ).

进而,将该体积电阻率为4.5×1014Ω·cm的基板埋入铁和碳酸锂的混合粉(Fe:Li2CO3=5:100bymass)之后,对混合粉中埋入的基板,常压下,氮100%氛围中,温度540℃进行6小时的热处理。Furthermore, after embedding the substrate having a volume resistivity of 4.5×10 14 Ω·cm in mixed powder of iron and lithium carbonate (Fe:Li 2 CO 3 =5:100bymass), the substrate embedded in the mixed powder is often Heat treatment was performed at a temperature of 540° C. for 6 hours in an atmosphere of 100% nitrogen under pressure.

此外,将热处理结束的基板的两面进行研磨,厚度0.2mm的钽酸锂单晶基板得到后,对该钽酸锂单晶基板,测定其体积电阻率,得知其值为7.3×1011Ω·cm~2.3×1012Ω·cm。该基板表面中,有色斑,基板的面内方向的均质性差。In addition, both sides of the heat-treated substrate were polished to obtain a lithium tantalate single crystal substrate with a thickness of 0.2 mm. The volume resistivity of the lithium tantalate single crystal substrate was measured and found to be 7.3×10 11 Ω ·cm~2.3×10 12 Ω·cm. On the surface of the substrate, there were stains, and the homogeneity in the in-plane direction of the substrate was poor.

在该比较例1中,钽酸锂单晶基板的还原处理仅为1回,为了充分进行还原,所以体积电阻率的最大值为2.3×1012Ω·cm,高,基板的面内方向的均质性也差。此外,碳酸锂和铁一起在混合粉中进行热处理,基板表面发生色斑。In Comparative Example 1, the reduction treatment of the lithium tantalate single crystal substrate was performed only once. In order to fully perform the reduction, the maximum value of the volume resistivity was 2.3×10 12 Ω·cm, which was as high as the in-plane direction of the substrate. The homogeneity is also poor. In addition, lithium carbonate and iron are heat-treated together in the mixed powder, and stains occur on the surface of the substrate.

比较例2Comparative example 2

比较例2中,首先,用切克劳斯基单晶生长法使钽酸锂单晶成长,得到的块体进行极化处理后,将其切片成多枚的基板。In Comparative Example 2, first, a single crystal of lithium tantalate was grown by the Czochralski single crystal growth method, and the resulting block was polarized and then sliced into a plurality of substrates.

然后,将该体积电阻率为4.5×1014Ω·cm的基板的两面进行研磨,厚度0.2mm的钽酸锂单晶基板得到后,对该钽酸锂单晶基板,测定波长365nm和波长485nm的光透过率,得知波长365nm的光透过率为72%,波长485nm的光透过率为75%。此外,对得到的基板的体积电阻率进行测定,其值为4.5×1014Ω·cm。Then, both sides of the substrate with a volume resistivity of 4.5×10 14 Ω·cm were polished to obtain a lithium tantalate single crystal substrate with a thickness of 0.2 mm. The lithium tantalate single crystal substrate was measured at a wavelength of 365 nm and a wavelength of 485 nm. According to the light transmittance, the light transmittance of wavelength 365nm is 72%, and the light transmittance of wavelength 485nm is 75%. Furthermore, the volume resistivity of the obtained substrate was measured and found to be 4.5×10 14 Ω·cm.

该比较例2中,由于没有实施钽酸锂单晶基板的还原处理,波长365nm的光透过率高达72%,体积电阻率也高达4.5×1014Ω·cm,不能得到满足之物。In Comparative Example 2, since the reduction treatment of the lithium tantalate single crystal substrate was not performed, the light transmittance at a wavelength of 365 nm was as high as 72%, and the volume resistivity was also as high as 4.5×10 14 Ω·cm, which were not satisfactory.

比较例3Comparative example 3

比较例3中,首先,用切克劳斯基单晶生长法使以重量比率计铁元素含有100ppm的钽酸锂单晶,得到的块体用极化处理后,切片得到多枚的基板。In Comparative Example 3, first, a single crystal of lithium tantalate containing 100 ppm by weight of iron was grown by the Czochralski single crystal growth method, and the obtained bulk was subjected to polarization treatment, and then sliced to obtain a plurality of substrates.

然后,将该体积电阻率为5.0×1013Ω·cm的基板的两面进行研磨,厚度0.2mm的钽酸锂单晶基板得到后,含该铁元素的钽酸锂单晶基板,进行波长365nm和波长485nm的光透过率的测定,得知波长365nm的光透过率为50%,波长485nm的光透过率为65%。此外,对得到的基板的体积电阻率进行测定和,得知其值为5.0×1013Ω·cm。Then, both sides of the substrate with a volume resistivity of 5.0×10 13 Ω·cm are ground to obtain a lithium tantalate single crystal substrate with a thickness of 0.2 mm. According to the measurement of the light transmittance at a wavelength of 485 nm, the light transmittance at a wavelength of 365 nm is 50%, and the light transmittance at a wavelength of 485 nm is 65%. Furthermore, the volume resistivity of the obtained substrate was measured and found to be 5.0×10 13 Ω·cm.

该比较例3中,由于没有对含铁元素的钽酸锂单晶基板进行还原处理,波长365nm的光透过率为50%,高,此外体积电阻率也为5.0×1013Ω·cm,高,没有得到满足之物。In Comparative Example 3, since no reduction treatment was performed on the iron-containing lithium tantalate single crystal substrate, the light transmittance at a wavelength of 365 nm was as high as 50%, and the volume resistivity was also 5.0×10 13 Ω·cm, High, nothing to satisfy.

比较例4Comparative example 4

比较例4中,首先,用切克劳斯基单晶生长法使以重量比率计含有铁元素为100ppm的钽酸锂单晶成长,得到的块体进行极化处理后,切片得到多枚的基板。此外,使通常的钽酸锂单晶基板暴露于1050℃的氢气,准备多区域化的基板。In Comparative Example 4, at first, a lithium tantalate single crystal containing 100 ppm of iron element was grown by the Czochralski single crystal growth method, and the obtained block was subjected to polarization treatment, and sliced to obtain multiple pieces. substrate. In addition, a general lithium tantalate single crystal substrate was exposed to hydrogen gas at 1050° C. to prepare a multi-region substrate.

然后,作为热处理的第一工序,含铁元素为100ppm的极化处理了的体积电阻率为5.0×1013Ω·cm的钽酸锂单晶基板和多区域化的钽酸锂单晶基板接触,进行常压下,氢100%氛围中,温度570℃的8小时的热处理。Then, as the first step of heat treatment, a polarized lithium tantalate single crystal substrate with a volume resistivity of 5.0×10 13 Ω·cm containing 100 ppm of iron is contacted with a multi-domain lithium tantalate single crystal substrate , under normal pressure, in an atmosphere of 100% hydrogen, heat treatment at a temperature of 570° C. for 8 hours.

进而,作为热处理的第二工序,以与第一工序和同样的处理条件进行热处理。Furthermore, as the second step of heat treatment, heat treatment was performed under the same treatment conditions as in the first step.

此外,对第一以及第二工序结束的基板的两面进行研磨,厚度0.2mm的钽酸锂单晶基板得到后,对该含铁元素钽酸锂单晶基板,测定波长365nm和波长485nm的光透过率,得知波长365nm的光透过率为25%,波长485nm的光透过率为45%。此外,对得到的基板的体积电阻率进行测定,其值为1.0×1011Ω·cm。In addition, after the first and second processes are finished, both sides of the substrate are polished to obtain a lithium tantalate single crystal substrate with a thickness of 0.2 mm, and the light with a wavelength of 365 nm and a wavelength of 485 nm is measured for the iron element-containing lithium tantalate single crystal substrate. As for the transmittance, it is known that the light transmittance at a wavelength of 365 nm is 25%, and that at a wavelength of 485 nm is 45%. Furthermore, the volume resistivity of the obtained substrate was measured and found to be 1.0×10 11 Ω·cm.

在该比较例4中,含铁元素的钽酸锂单晶基板实施了还原处理,但是,第二工序中,第一工序结束的原料基板没有与碳酸锂一起进行热处理,波长485nm的光透过率为比50%小的45%,没有得到满足之物。In this comparative example 4, the iron element-containing lithium tantalate single crystal substrate was subjected to reduction treatment, but in the second step, the raw material substrate after the first step was not heat-treated together with lithium carbonate, and the light with a wavelength of 485 nm was transmitted. The rate is 45%, which is less than 50%, and there is no satisfaction.

Claims (7)

1. a kind of manufacture method of monocrystalline lithium tantalate substrate, the specific insulation of the monocrystalline lithium tantalate substrate is 1 × 1010Ω· More than cm, 1 × 1012Ω cm less than, it is characterised in that including specific insulation be 1 × 1012More than Ω cm, and will be single At ambient pressure, in hydrogen atmosphere, more than 400 DEG C, the temperature below Curie temperature carries out heat to tectonic monocrystalline lithium tantalate substrate Processing the first process and, the monocrystalline lithium tantalate substrate that will be handled in first process, together with lithium carbonate, under normal pressure, hydrogen or In nitrogen atmosphere, more than 400 DEG C, the second process that the temperature below Curie temperature is heat-treated.
2. the manufacture method of monocrystalline lithium tantalate substrate according to claim 1, it is characterised in that in first process, make The specific insulation is 1 × 1012More than Ω cm, and single tectonic monocrystalline lithium tantalate substrate, and in reproducibility gas In atmosphere, the monocrystalline lithium tantalate substrate contact of the multi-region domain construction of temperature heat treatment more than Curie temperature is carried out at the heat Reason.
3. according to the manufacture method of the monocrystalline lithium tantalate substrate of claim 1 or 2, it is characterised in that in second process, The heat treatment is carried out in nitrogen atmosphere.
4. according to the manufacture method of the monocrystalline lithium tantalate substrate of any one of claims 1 to 3, it is characterised in that described In two processes, the monocrystalline lithium tantalate substrate of first process processing is embedded in lithium carbonate powder.
5. according to the manufacture method of the monocrystalline lithium tantalate substrate of any one of Claims 1-4, it is characterised in that the tantalic acid Lithium monocrystal substrate, is used as addition element iron content.
6. the manufacture method of monocrystalline lithium tantalate substrate according to claim 5, it is characterised in that the amount of above-mentioned iron is, 50ppm~200ppm.
7. according to the manufacture method of the monocrystalline lithium tantalate substrate of claim 5 or 6, it is characterised in that the specific insulation is 1 ×1010More than Ω cm, 1 × 1012Ω cm less than monocrystalline lithium tantalate substrate, wavelength 365nm light transmission rate be 30% Hereinafter, it is more than 50% in wavelength 485nm light transmission rate.
CN201710003835.6A 2016-01-07 2017-01-04 Manufacturing method of lithium tantalate single crystal substrate Active CN106948005B (en)

Applications Claiming Priority (2)

Application Number Priority Date Filing Date Title
JP2016-001506 2016-01-07
JP2016001506A JP6256955B2 (en) 2016-01-07 2016-01-07 Method for producing lithium tantalate single crystal substrate

Publications (2)

Publication Number Publication Date
CN106948005A true CN106948005A (en) 2017-07-14
CN106948005B CN106948005B (en) 2022-02-25

Family

ID=59306488

Family Applications (1)

Application Number Title Priority Date Filing Date
CN201710003835.6A Active CN106948005B (en) 2016-01-07 2017-01-04 Manufacturing method of lithium tantalate single crystal substrate

Country Status (2)

Country Link
JP (1) JP6256955B2 (en)
CN (1) CN106948005B (en)

Cited By (2)

* Cited by examiner, † Cited by third party
Publication number Priority date Publication date Assignee Title
CN114318538A (en) * 2020-09-28 2022-04-12 信越化学工业株式会社 Method for producing lithium tantalate single crystal substrate
CN114836836A (en) * 2022-06-23 2022-08-02 济南大学 Local rapid blackening method for lithium niobate wafer/lithium tantalate wafer

Families Citing this family (2)

* Cited by examiner, † Cited by third party
Publication number Priority date Publication date Assignee Title
JP6238478B2 (en) * 2016-03-16 2017-11-29 信越化学工業株式会社 Method for producing lithium tantalate single crystal substrate
JP7131378B2 (en) * 2018-12-27 2022-09-06 住友金属鉱山株式会社 Single crystal wafer manufacturing method

Citations (3)

* Cited by examiner, † Cited by third party
Publication number Priority date Publication date Assignee Title
CN1754014A (en) * 2003-03-06 2006-03-29 信越化学工业株式会社 Process for producing lithium tantalate crystal
CN1950549A (en) * 2004-04-27 2007-04-18 山寿瑟拉密克斯株式会社 Charge restraining method and apparatus for piezoelectric oxide single crystal
CN101608342A (en) * 2009-07-27 2009-12-23 中电科技德清华莹电子有限公司 A method for processing lithium niobate or lithium tantalate wafers

Family Cites Families (6)

* Cited by examiner, † Cited by third party
Publication number Priority date Publication date Assignee Title
JP2862742B2 (en) * 1993-01-14 1999-03-03 日本碍子株式会社 Method for producing oxide single crystal
JPH1135393A (en) * 1997-05-19 1999-02-09 Hitachi Metals Ltd Stoichiometric composition lithium tantalate single crystal, method for producing the same and optical device
JP2005119907A (en) * 2003-10-16 2005-05-12 Sumitomo Metal Mining Co Ltd Lithium tantalate substrate and its producing method
JP4924818B2 (en) * 2007-02-22 2012-04-25 住友金属鉱山株式会社 Lithium tantalate substrate and manufacturing method thereof
JP5133279B2 (en) * 2009-01-27 2013-01-30 信越化学工業株式会社 Method for producing lithium tantalate crystals
JP6327089B2 (en) * 2014-09-29 2018-05-23 住友金属鉱山株式会社 Filling equipment

Patent Citations (3)

* Cited by examiner, † Cited by third party
Publication number Priority date Publication date Assignee Title
CN1754014A (en) * 2003-03-06 2006-03-29 信越化学工业株式会社 Process for producing lithium tantalate crystal
CN1950549A (en) * 2004-04-27 2007-04-18 山寿瑟拉密克斯株式会社 Charge restraining method and apparatus for piezoelectric oxide single crystal
CN101608342A (en) * 2009-07-27 2009-12-23 中电科技德清华莹电子有限公司 A method for processing lithium niobate or lithium tantalate wafers

Cited By (2)

* Cited by examiner, † Cited by third party
Publication number Priority date Publication date Assignee Title
CN114318538A (en) * 2020-09-28 2022-04-12 信越化学工业株式会社 Method for producing lithium tantalate single crystal substrate
CN114836836A (en) * 2022-06-23 2022-08-02 济南大学 Local rapid blackening method for lithium niobate wafer/lithium tantalate wafer

Also Published As

Publication number Publication date
CN106948005B (en) 2022-02-25
JP6256955B2 (en) 2018-01-10
JP2017122024A (en) 2017-07-13

Similar Documents

Publication Publication Date Title
US7323050B2 (en) Method of producing lithium tantalate crystal
JP2005206444A (en) Lithium tantalate substrate and manufacturing method thereof
EP1939333A1 (en) Ferroelectric single crystal, surface acoustic filter making use of the same and process for producing the filter
JP2019156655A (en) Method for manufacturing lithium tantalate substrate
CN106948005B (en) Manufacturing method of lithium tantalate single crystal substrate
JP4937178B2 (en) Method for producing lithium tantalate crystals
CN107201544A (en) The manufacture method of monocrystalline lithium tantalate substrate
EP1518947A2 (en) Method of producing single-polarized lithium tantalate crystal and crystal thereby obtained.
CN106533386A (en) Melilite structure crystal zero/ near-zero frequency temperature coefficient cut and processing method and application thereof
JP2018080088A (en) Method for manufacturing lithium tantalate single crystal substrate and lithium tantalate single crystal substrate
JP2020040840A (en) Method for producing lithium tantalate substrate
JP2005317822A (en) Method for producing unipolarized lithium tantalate
JP2019112267A (en) Method for manufacturing lithium tantalate substrate
JP2020011874A (en) Manufacturing method of lithium tantalate substrate
JP4596149B2 (en) Method for producing lithium tantalate crystals
JP6186099B1 (en) Surface acoustic wave device substrate and method of manufacturing the same
JP4482761B2 (en) Method for producing lithium tantalate crystals
JP6959886B2 (en) Crystal manufacturing method
JP7082317B2 (en) Manufacturing method of lithium tantalate substrate
JP2021116194A (en) Manufacturing method of lithium tantalate substrate
WO2017068810A1 (en) Method for producing lithium niobate single crystal substrate
KR102601394B1 (en) Lithium niobate single crystal substrate and manufacturing method thereof
WO2006051610A1 (en) Method for producing lithium tantalate crystal
KR20180019550A (en) Lithium niobate single crystal substrate and manufacturing method thereof
JP2005119950A (en) Method for producing unipolarized lithium tantalate crystals and unipolarized lithium tantalate crystals

Legal Events

Date Code Title Description
PB01 Publication
PB01 Publication
SE01 Entry into force of request for substantive examination
SE01 Entry into force of request for substantive examination
GR01 Patent grant
GR01 Patent grant